ChemInform Abstract: [Te8][NbOCl4]2 Containing an Infinite Chain‐Like [Te—Te—Te—(Te5)]2+n Polycation. Issue 1 (3rd January 2013) - Feldmann, Claus; Freudenmann, Dominic
Abstract Translucent black crystals of the title compound are obtained from mixtures of Te, NbCl5, and NbOCl3 in the ionic liquid [bmim]Cl (Ar filled glass ampules, 423 K, 14 d; 30% yield).